Bioink: a 3D-bioprinting tool for anticancer drug discovery and cancer management - Tiwari, Arpita P; Thorat, Nanasaheb D; Pricl, Sabrina; Patil, Rakesh M; Rohiwal, Sonali; Townley, Helen (Drug discovery today, 2021)
'Bioinks' are important tools for the fabrication of artificial living-tissue constructs that are able to mimic all properties of native tissues via 3D bioprinting technologies. Bioinks are most commonly made by incorporating live cells of interest within a natural or synthetic biocompatible polymeric matrix. In oncology research, the ability to recreate a tumor microenvironment (TME) using by 3D bioprinting constitutes a promising approach for drug development, screening, and in vitro cancer modeling. Here, we review the different types of bioink used for 3D bioprinting, with a focus on its application in cancer management. In addition, we consider the fabrication of bioink using customized materials/cells and their properties in the field of cancer drug discovery.
Keywords: Drug Discovery; nádory; 3D tisk; Humans; Animals; Printing, Three-Dimensional; lidé; objevování léků; protinádorové látky; bioprinting; Neoplasms; Bioprinting; zvířata; Antineoplastic Agents